2016
DOI: 10.1097/md.0000000000002726
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Reduced Risk of Intracerebral Hemorrhage and Pelvic Inflammatory Disease

Abstract: This study examines whether pelvic inflammatory disease (PID) facilitates the development of intracerebral hemorrhage (ICH).By using outpatient claims data from the National Health Insurance Research Database (NHIRD) of Taiwan, we included the data of 25,508 patients who were newly diagnosed with PID between 1999 and 2004, and also from the Taiwan NHIRD, we randomly selected 102,032 women without PID, who were frequency-matched by age and entry-year and with 4 times the number of the PID patients, as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…In patients with diabetes, due to abnormal glucose metabolism, the bodys energy supply is unbalanced, and the immunity is reduced, thus infection is more likely to occur. [ 35 ] Previous studies [ 36 ] have shown that people with poor glycemic control are at higher risk of infection. GCS is an important indicator of the functions of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diabetes, due to abnormal glucose metabolism, the bodys energy supply is unbalanced, and the immunity is reduced, thus infection is more likely to occur. [ 35 ] Previous studies [ 36 ] have shown that people with poor glycemic control are at higher risk of infection. GCS is an important indicator of the functions of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also focused on the association of PID with specific cardiovascular diseases. [18,19] For instance, research from Taiwan indicated that patients with PID had a higher likelihood of myocardial infarction compared to controls. [20] However, understanding the association between CVD and PID requires consideration of the shared pathogenesis and common risk factors between these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature suggests that all the previously published studies evaluating the risk of cardiovascular outcomes among women with a history of PID were from Taiwan [ 5 , 6 , 36 ]. The Taiwanese studies noted that compared to women without history of PID, women with history of PID were at a significantly higher risk of myocardial infarction and ischaemic stroke but at a significantly lower risk of intracerebral haemorrhage.…”
Section: Discussionmentioning
confidence: 99%